Causal Loop Diagram Analysis of Stunting Specific Intervention for Policy Recommendation: A Case from Pekalongan Regency Indonesia - Yuniarti, Yuniarti; Bintari, Siti Harnina; Zainafree, Intan (Universitas Negeri Semarang, 2025)
Stunting is still a global health issue, especially in lower-middle class countries, the problem of stunting reflects a multidimensional problem that has not been addressed effectively. In Indonesia, the prevalence of stunting has decreased significantly by 18.9% in 2023, but has not reached the target set at 14%. This study is a qualitative study with a causal loop diagram analysis approach, the causal loop diagram method was chosen because it is able to describe problems that interact dynamically as causality. Data collection by interviewing 23 informants and analyzing documents on the achievement of specific interventions in 2023 from the Pekalongan District Health Office. There are five key variables identified, namely the ability of officers, specific interventions, budget, community roles and access to health services. The results of the CLD analysis formed 26 causal links, strengthening one loop and balancing two loops. The findings highlight the disparity in access to health services and the role of the community that is not yet optimal. Policy recommendations, improve cross-sector coordination to improve the provision of health services and increase the role of the community, especially mothers of toddlers and cadres in specific nutrition interventions. The use of CLD analysis in holistic and strategic specific nutritional interventions in identifying stunting problems to determine the most appropriate interventions.